Deconstructing Anthropocentric Sustainability: A Post-Anthropocentric Critique of Halal Tourism Ecosystem - Mohammad Aliman Shahmi; Yuliza Zen; Rizal Rizal; Chitra Indah Sari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Background: Halal tourism has expanded rapidly, often adopting the narrative of